LAJU PERTUMBUHAN DAN KEPADATAN MIKROALGA Dunaliella sp. PADA PEMBERIAN TIMBAL ASETAT DENGAN KONSENTRASI YANG BERBEDA - Fitly Tewal; Kurniati Kemer; Joice R.T.S.L. Rimper; Desy M.H. Mantiri; Wilmy E Pelle; Joppy D Mudeng (JURNAL PESISIR DAN LAUT TROPIS, 2021)
Microalgae are organisms that contain chlorophyll and other pigments so they can carry out photosynthesis. Microalgae are widespread in nature and can be found in any environment exposed to sunlight. Microalgae are micro-sized biota with a diameter of less than 2 Âµm. The benefits of microalgae for other living things, especially humans, are numerous, including as a source of food and ingredients in the manufacture of medicines. Dunaliella sp. is a group of green algae that contains protein, fat and carbohydrates as a good source of food. Growth rate and density of microalgae Dunaliella sp. and the effect of lead acetate with different concentrations was observed using a microscope, starting from the lag phase, the logarithmic phase, the stationary phase and the declination phase. Dunaliella sp. Experiencing an exponential phase in the observation before treatment, namely on the 9th day and then doing the treatment. Treatment with lead acetate with concentrations of 10 ppm, 50 ppm and 80 ppm is very influential in the growth of microalgae. The result is that lead acetate contains toxins that can kill microalgae cells in both low and high concentrations.Keywords: Microalgae, Dunaliella sp., Lead Acetate, Concentration